Rapid assessment of knowledge, attitudes, practices, and risk perception related to the prevention and control of Ebola virus disease in three communities of Sierra Leone. Issue 1 (December 2016) - Jiang, Hai; Shi, Guo-Qing; Tu, Wen-Xiao; Zheng, Can-Jun; Lai, Xue-Hui; Li, Xin-Xu; Wei, Qiang; Li, Mei; Deng, Li-Quan; Huo, Xiang; Chen, Ming-Quan; Xu, Feng; et al.
Abstract Background The recent outbreak of the Ebola virus disease (EVD) in Sierra Leone has been characterized by the World Health Organization as one of the most challenging EVD outbreaks to date. The first confirmed case in Sierra Leone was a young woman who was admitted to a government hospital in Kenema following a miscarriage on 24 May 2014. On 5 January 2015, intensified training for an EVD response project was initiated at the medical university of Sierra Leone in Jui. To understand the knowledge, attitudes, practices, and perceived risk of EVD among the public, especially after this training, a rapid assessment was conducted from 10 to 16 March 2015. Methods Interviews were conducted with 466 participants based on questionnaires that were distributed from 10 to 16 March 2015 by cluster sampling in three adjacent communities, namely Jui, Grafton, and Kossoh Town, in the Western Area Rural District of Sierra Leone. Results It was found that knowledge about EVD was comprehensive and high. Positive attitude towards prevention was found to be satisfactory. Nearly all participants knew the reporting phone number 117 and had reported some change in behavior since learning about Ebola. More than half (62 %) of the participants had a history of travelling to urban areas, which increases the risk of infection. The multivariable logistic regression analysis showed that community and occupation were variables associated with perceived risk of EVD. Conclusions Our study showed that community level social mobilization and community engagement were an effective strategy in the special context.